Negative Pressure in the Treatment of Odontogenic Inflammation - R. Pink; M. Šimek; P. Michl; P. Tvrdý; J. Pazdera (Czech Dental Chamber, 2013)
Introduction: Odontogenic inflammation is a fairly common condition, and depends on the quality of oral health. Unfortunately, the incidence in the Czech population is increasing. It is also sometimes connected with life-threatening complications. Aim: To describe an unusual method of treating phlegmonous inflammation of the mouth floor and neck, complicated by necrotizing fasciitis.Material and Method, Results: The authors demonstrate a strategy of treating odentogennic phlegmonous inflammation of the mouth floor in a patient with a blood coagulation disorder and advanced liver cirrhosis. The course of treatment was complicated by a massive gastric ulcer bleeding and due to the large necrosis of the soft tissue of the neck. Application of local negative pressure was used successfully. Conclusion: The local application of negative pressure in the surgical treatment of necrotizing fasciitis in the head and neck region is not very common. Recently, a number of authors have described the feasibility of this procedure in this anatomical location. The main advantages are, among others, shorter and less costly treatment and reduced stress for medical staff.